2010
DOI: 10.1111/j.1524-4725.2010.01615.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonmelanoma Skin Cancer of the Ear: Frequency, Patients' Knowledge, and Photoprotection Practices

Abstract: Directed public education about the ear as a high-risk, common site for NMSC is needed. The authors have indicated no significant interest with commercial supporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…1215 These studies generally found that individuals with dark skin types practiced photoprotection less frequently than those with light skin. 13 In our CLE population, overall SPH scores were significantly lower for the medium-skinned (i.e. skin types III–IV) and dark-skinned (i.e.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…1215 These studies generally found that individuals with dark skin types practiced photoprotection less frequently than those with light skin. 13 In our CLE population, overall SPH scores were significantly lower for the medium-skinned (i.e. skin types III–IV) and dark-skinned (i.e.…”
Section: Discussionmentioning
confidence: 65%
“…13, 15 The gender difference in photoprotective habits may be attributed to cultural customs. However, the photoprotective methods favored by men may not be as effective as those methods favored by women.…”
Section: Discussionmentioning
confidence: 99%
“…SCC is a common cutaneous tumor with a steadily rising incidence rate predominantly affecting sun‐sensitive individuals with years of chronic sun exposure . Of head and neck locations, the ear is the fifth most common location for SCC but represent a high‐risk area for metastasis . Approximately 5% to 10% of newly diagnosed skin cancers are located on the ear .…”
Section: Discussionmentioning
confidence: 99%
“…10 Of head and neck locations, the ear is the fifth most common location for SCC but represent a high-risk area for metastasis. [11][12][13][14] Approximately 5% to 10% of newly diagnosed skin cancers are located on the ear. 15 In the setting of recurrent invasive SCC of the ear, approximately 45% of patients will demonstrate nodal metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation